Carbon nanodots-based C-dips for rapid colorimetric detection of clinically important metal ions - Sumaira Nishat; Malik Waseem Abbas; Fazli Rabbi Awan; Dr Razium Ali Soomro (Kuwait Journal of Science)
Owing to unique physical and optical properties, fluorescent carbon dots (C-dots) are used in various biomedical applications. In this study, C-dots have been integrated as sensing agent on paper surface for colorimetric determination of clinically important analytes. Polyacrylamide-based C-dots coated C-dips showed visible color change from white to brown for iron (Fe2+, Fe3+) sample. Moreover, iron and copper (Cu2+) samples showed significant quenching of C-dots under UV. Images captured with/without UV were analyzed to study the relationship between different iron and copper concentrations and colorimetric intensity values. Color intensity and fluorescence showed a linear relationship with concentrations of iron and copper (Range: 1×10-4 to 1×10-2 M, Linearity: R2 = 0.94). LOD from the paper sensor showed a sensitivity of 3.89×10-5 μM, 4.65×10-5 μM and 6.7×10-5 μM for Fe3+, Fe2+ and Cu2+ respectively, reflecting its reliability as low-cost sensing solution to analyze clinically relevant analytes as reported in current study.